A New Report of Leaf Vein Gall on Madhuca longifolia (Sapotaceae) from India - Kumar, Arvind; Singh, Sudhir (Indian Forester, 2018)
The leaf vein gall symptoms were observed first time on multipurpose tree Madhuca lonigifolia leaves to be infested with an unknown insect. This infestation was reported for the first time from Ranchi in the year 2012 and later it was observed in many districts of Jharkhand. In the year 2015 the same vein gall formation was recorded at FRI Campus Dehradun, Uttarakhand. The plant and leaf infestation, their morphology has been discussed in this paper.